Erythrocyte Encapsulated Thymidine Phosphorylase for the Treatment of Patients with Mitochondrial Neurogastrointestinal Encephalomyopathy: Study Protocol for a Multi-Centre, Multiple Dose, Open Label Trial - Bax, Bridget E. (J Clin Med, 2019)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is an autosomal recessive disorder which primarily affects the gastrointestinal and nervous systems. This disease is caused by mutations in the nuclear TYMP gene, which encodes for thymidine phosphorylase, an enzyme required for the normal metabolism of deoxynucleosides, thymidine, and deoxyuridine. The subsequent elevated systemic concentrations of deoxynucleosides lead to increased intracellular concentrations of their corresponding triphosphates, and ultimately mitochondrial failure due to progressive accumulation of mitochondrial DNA (mtDNA) defects and mtDNA depletion. Currently, there are no treatments for MNGIE where effectiveness has been evidenced in clinical trials. This Phase 2, multi-centre, multiple dose, open label trial without a control will investigate the application of erythrocyte-encapsulated thymidine phosphorylase (EE-TP) as an enzyme replacement therapy for MNGIE. Three EE-TP dose levels are planned with patients receiving the dose level that achieves metabolic correction. The study duration is 31 months, comprising 28 days of screening, 90 days of run-in, 24 months of treatment and 90 days of post-dose follow-up. The primary objectives are to determine the safety, tolerability, pharmacodynamics, and efficacy of multiple doses of EE-TP. The secondary objectives are to assess EE-TP immunogenicity after multiple dose administrations and changes in clinical assessments, and the pharmacodynamics effect of EE-TP on clinical assessments.